Forest and landscape restoration severely constrained by a lack of attention to the quantity and quality of tree seed: Insights from a global survey - Jalonen, R.; Valette, M.; Boshier, D.; Duminil, J.; Thomas, E. (Wiley, 2018)
Meeting the multimillion hectare commitments for forest and landscape restoration (FLR) will require billions of tree seed and seedlings. However, the adequacy of seed supply in terms of quantity, genetic diversity and quality has received scant attention in FLR planning. We surveyed 139 FLR projects worldwide and identified widespread problems in the availability and diversity of tree seed, with potentially deleterious consequences for the vigor, productivity and long-term persistence of restored tree populations. Large projects and those focused on climate change mitigation were particularly associated with multiple problems in seed sourcing. To avoid large-scale failure in FLR, we recommend: (1) national assessments of seed supply and demand for FLR, (2) reviewing FLR targets and funding cycles, (3) fostering sharing of knowledge and experiences regarding seed supply and selection, (4) enhancing seed exchange across landscapes, and (5) introducing regulations for seed quality and strengthening capacities for compliance.